2016
DOI: 10.1142/s0218271816500024
|View full text |Cite
|
Sign up to set email alerts
|

Numerically fitting the electron Fermi energy and the electron fraction in a neutron star

Abstract: Based on the basic definition of the Fermi energy of degenerate and relativistic electrons, we obtain a special solution to the electron Fermi energy, [Formula: see text], and express [Formula: see text] as a function of the electron fraction, [Formula: see text], and matter density, [Formula: see text]. We obtain several useful analytical formula for [Formula: see text] and [Formula: see text] within classical models and the work of Dutra et al. (2014) (Type-2) in relativistic mean-field theory are obtained u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…It is interesting to mention that Gao et al (2013) and Zhu et al (2016) made a great deal of deliberations in this direction, particularly in the study of how the Fermi energy and the electron degeneracy pressure change in a neutron star due to the presence of a strong magnetic field. Gao et al (2013) and Li et al (2016) indicated that in the presence of a strong magnetic field the electron degeneracy pressure increases with strength of the magnetic field. This is because the pressure is proportional to E 4 F and the Fermi energy E F increases with the strength of the magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to mention that Gao et al (2013) and Zhu et al (2016) made a great deal of deliberations in this direction, particularly in the study of how the Fermi energy and the electron degeneracy pressure change in a neutron star due to the presence of a strong magnetic field. Gao et al (2013) and Li et al (2016) indicated that in the presence of a strong magnetic field the electron degeneracy pressure increases with strength of the magnetic field. This is because the pressure is proportional to E 4 F and the Fermi energy E F increases with the strength of the magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…As we know, the maximum NS mass predicted by EOSs is model dependent (e.g., Dutra et al 2014;Li et al 2016;Xia et al 2016;Xia & Zhou 2017;Zhou et al 2017). The largest sample of measured NS masses available for analysis is publicly accessible online at http://www.stellarcollapse.org/ and has been updated by J. Lattimer.…”
Section: Nuclear Eos and Moment Of Inertiamentioning
confidence: 99%
“…Our previous work (Li et al ) (“Li16” in short) was devoted to considering the electron Fermi energy and an associated value of the electron number fraction as functions of the matter density ρ within different layers of NS's crust and core of a common NS with B ≪ B cr (Li et al ; Gao et al ). Since the main purpose of this paper is to reinvestigate Y e and E F ( e ) inside an NS by revising Li16, it is necessary to briefly review Li16, which is provided below.…”
Section: Introductionmentioning
confidence: 99%